The Impact of Point Cloud Simplification on the Accuracy of the Viewshed - ORLOF, Jerzy; WIDŁAK, Adrian (Computer Assisted Methods in Engineering and Science, 2026)
Contemporary visibility analyses, particularly relevant in environmental and landscape studies, require the processing of very large datasets derived from point clouds. While such data provide high accuracy, they also involve substantial computational demands and long processing times, which limit their practical applicability. This article presents a detailed analysis of the impact of point cloud simplification on the accuracy of viewshed. The viewshed diagrams were generated using the ray tracing method, and the analysis included an evaluation of discrepancies between results obtained from simplified datasets and reference outcomes based on the complete, unprocessed dataset. In addition, the computation time required to generate viewshed under different levels of simplification was investigated. The findings made it possible to identify the maximum acceptable levels of simplification as well as the potential computational gains in terms of the number of processed points. The results demonstrate that properly selected simplification levels can significantly enhance the efficiency of ray tracing-based visibility analyses while preserving their practical reliability.